Pseudoaneurysm following aortic homograft: clinical implications?. Issue 6 (December 1995) - Oechslin, E.; Carrel, T.; Ritter, M.; Attenhofer, C.; von Segesser, L.; Kiowski, W.; Turina, M.; Jenni, R.
Abstract : OBJECTIVE--To determine the prevalence of pseudoaneurysm formation after aortic (left ventricular outflow tract) homograft implantation and to evaluate predisposing factors. METHODS--Echocardiographic data were analysed in 30 patients for evidence of pseudoaneurysm formation after homograft implantation. Pseudoaneurysm was characterised as a perfused echo-free space between the homograft and the native aortic wall communicating with the left ventricular outflow tract. Clinical data were analysed for potential predisposing factors for pseudoaneurysm formation. RESULTS--Pseudoaneurysms were found in 22 of 30 patients. Mean age, length of follow up after surgery, aortic systolic pressure gradient (15 (SD 12) v 10 (4) mm Hg), aortic root diameter, and size of the homografts were comparable in patients with and without pseudoaneurysm. preoperative infection, operating techniques, and whether first or reoperation did not affect pseudoaneurysm formation. However, pseudoaneurysms were often localised at the site of an abscess or a paravalvular leak after eradicated prosthetic valve endocarditis. CONCLUSIONS--(1) Doppler echocardiography demonstrates that pseudoaneurysm formation is common after aortic homograft implantation. (2) A prospective study is needed to clarify the prognostic importance of pseudoaneurysms. (3) The high incidence of pseudoaneurysm formation may lead to an improvement of surgical technique (application of fibrin glue).